Curbing the trade in pangolin scales in China by revealing the characteristics of the illegal trade network - Fei Xi; Xiaoran Chao; Shibao Wu; Fuhua Zhang (Scientific Reports)
Abstract Globally, pangolins are the most heavily trafficked mammals and China is one of the main destinations for their scales and meat. Conducting separate studies on the characteristics of the illegal trade in pangolin meat and in scales in China will provide a basis for devising more targeted protection strategies and actions. This study focused on the illegal pangolin-scale trading network in China by collating relevant cases of smuggling published in China Judgements Online, revealing that most scales came from Africa. The six main cities involved in the illegal trade in China were Bozhou, Chongzuo, Dehong, Beijing, Hong Kong, and Kunming. Seizures of illegally traded scales have decreased significantly due to strengthened law enforcement and increased public awareness of their protected status. We recommend that, in addition to advocating for stronger pangolin protection legislation and law enforcement in Africa, the inspection in China of cargo and baggage on ships and aircraft from Africa and of trucks entering and leaving Bozhou City should also by strengthened, as should the raising of awareness of pangolin protection among express delivery personnel, and in particular, practitioners of traditional Chinese medicine should be discouraged from using pangolin scales in treatments. These measures will further effectively curb the illegal trade in pangolins in China.